EPIDEMIOLOGY OF NEURAL TUBE DEFECTS IN THE WORLD AND IRAN - D.D. Farhud; V. Hadavi; H. Sadighi (Tehran University of Medical Sciences, 2000)
Statistical data from 1966 till 1995 showed that Neural tube defects, in the American continent, Venezuela had the highest prevalence of 38.9 and some Latin American countries showed the low of 7.7. In Europe, Norway had the highest prevalence of 68, and Denmark the lowest, 5.8. In Asia, India had the highest of 181.8 and Japan the lowest of 10. In Africa, Nigeria had the highest of 70 and Negroes of South Africa had the lowest of 9.9. In Australia the figure was 20.05. According to the statistics available of the years 1967 till 1996, anencephaly in China had the highest prevalence of 87. In the American continent, state of Michigan in the USA had the highest of 10.5 and Jamaica, in Central America, had the lowest of 2.6. In Europe, Turkey with 16.4 and Italy with 2.73; in Asia, China with 87 and Iran with 0.8 had the highest and the lowest prevalence, respectively. In Africa, Nigeria with 3.5, and in Oceania, Newzeland with 7.8 in 10000, were reported. Data available on spina bifida, from the years 1968 till 1991 showed the highest prevalence in China with 36, and the lowest in the Alps Mountains with 0.55 in 10000 individuals. In the American continent, state of Arkansas with 7.8 and California with 3.87; in Europe, England with 23.1 and Rhein-Alp with 0.55 in 10000 had the highest and the lowest prevalence. Finally, in China this rate was 36, in Australia 10, in Newzeland 9.4, and in Nigeria 7/10000. In a study carried out in Tehran, from 1969 till 1978 by the authors, out of 13037 births, (17.6 in 10000) newborns had neural tube defects, with anencephaly 0.8 and spina bifida 3.8/10000. In a new study on 8585 deliveries (1991-1997) in Hamadan (a North West province of Iran), Prevalence of total NTDs was 50.1/10000, anencephaly 15.6 and spin bifida 6.98.